Aproximación a la percepción de los orientadores escolares sobre la colaboración que reciben de la comunidad educativa: retos y propuestas - García Nieto, Narciso; Cano Escoriaza, Jacobo (Revista Complutense de Educación, 2010)
The paper analyzes the perceptions of school counsellors on the support received from the school community. This is the first empirical study conducted in the region of Aragon on this subject. School counsellors face the challenge of dynamizing the teamworking, from a collaborative, systemic and interdisciplinary approach. The group of course tutors is the one that offers better general results, and specially, on implication matters. It is urgent that the government bodies and school management bodies recognize the different roles played by school counsellors. The high expectations of school counsellors on the collaboration with families -diagnosis and professional guidance- and students -professional guidance, diagnosis and teaching- are finally analyzed.